Studi Literatur Potensi Antibakteri Tanaman Sawo (Manilkara zapota (L.) P. Royen) terhadap Bakteri Penyebab Infeksi Saluran Pencernaan - Ulfah Cahyameta Siswoyo; Sri Peni Fitrianingsih; Siti Hazar (UNISBA Press, 2022)
Abstract. Bacteria is one of the causes of world health problems commonly called bacterial infections. One of the most common bacterial infections is a digestive tract infection. Bacterial infections can be treated with antibiotics. There are many plants that have antibacterial activity, one of which is sapodilla (Manilkara zapota (L.) P. Royen). The purpose of this literature study was to determine the antibacterial potential of sapodilla plants against bacteria that cause digestive tract infections and the class of compounds contained in sapodilla plants. The study was conducted using the Systematic Literature Review (SLR) method in reputable research journals using the keyword